Glorious Vices? Reconsidering Augustine's View of Pagan Virtue - Couenhoven, Jesse (Studies in Christian ethics, 2025)
St. Augustine famously argued that those who do not orient their loves toward God lack true virtue, offering as a test case pagan sages who cared too much for their own honor. For this polemic he has been lauded and lambasted; however, in significant ways, I contend, he has been misunderstood. A close reading of Augustine in his historical context helps us understand him as a revisionary yet committed classical eudaimonist, whose attack on pagan virtue was an immanent critique of views attractive to many Christians, including his younger self. This approach reveals the complexity of his relationship to pagan virtue theory and suggests that Augustine's modern readers have overestimated the severity of his critique. Although Augustine came to think of true virtue as a theological good that can only be had in grateful dependence on God, he also drew on little-noticed neo-Platonic traditions that distinguished perfect, true virtue, from civic virtues that are imperfect but nonetheless worthy of praise. This allowed him to admire pagan exemplars while critiquing the lack of compassion and humility that vitiated both their understanding of greatness and their ability to promote lasting communal flourishing.